Physical Education Students' Knowledge and Motivation in Lesson Study and Conventional Classes Using Audio-Visual-Supported Learning - Suharti; Lalu Moh Yudha Isnaini; Mulyono (Universitas Sulawesi Barat, 2026)
The success of learning in physical education is shaped by teaching methods that enhance both cognitive abilities and motivation among students. This research aimed to investigate how the lesson study approach, applied in a learning environment enriched with audio-visual resources, impacts students' understanding and motivation in physical education. A quantitative post-test-only comparison group design was utilized, involving 76 physical education students from Universitas PGRI Adi Buana Surabaya. Participants were assigned to either a conventional learning group (n = 38) or a lesson study group (n = 38), both receiving instruction enriched by audio-visual materials. Data were gathered through a structured knowledge test and the Expectancy-Value Questionnaire. The analysis employed independent-samples t-tests, with a significance threshold set at p < 0.05. The findings revealed that students in the lesson study group scored significantly higher on knowledge assessments compared to those in the conventional group (87.5 vs. 73.5; p = 0.01). Conversely, motivation scores were marginally greater for the lesson study group than for the conventional group (4.8 vs. 4.6), although this difference lacked statistical significance (p = 0.62). These results suggest that the implementation of lesson study in an audio-visual-supported learning context is linked to improved knowledge performance for physical education students, while its impact on learning motivation did not show statistical support.